The Role of Optical Coherence Tomography in an Atypical Case of Oculocutaneous Albinism: A Case Report - Settimio Rossi; Francesco Testa; Annagiusi Gargiulo; Valentina Di Iorio; Raffaella Brunetti Pierri; Francesco Maria D’Alterio; Michele Della Corte; Enrico Surace; Francesca Simonelli (Case Reports in Ophthalmology, 2012)
Background: Oculocutaneous albinism is a group of autosomal recessive disorders featuring hypopigmentation of the hair, skin and eyes. Ocular signs associated with the disease are nystagmus, decreased visual acuity, hypopigmentation of the retina, foveal hypoplasia, translucency of the iris, macular transparency, photophobia and abnormal decussation of nerve fibers at the chiasm. Case Report: An 8-year-old Caucasian girl presented to our clinic ‘Referral Center for Hereditary Retinopathies’ of the Second University of Naples with a diagnosis of Stargardt disease and a progressive reduction in visual acuity in both eyes. She underwent a complete ophthalmic examination including standard electroretinography and optical coherence tomography (OCT). A molecular analysis was also performed. Best-corrected visual acuity was 20/30 in the right eye and 20/40 in the left eye. Biomicroscopy of the anterior segment revealed a transparent cornea, in situ and transparent lens and normally pigmented iris. A mild diffuse depigmentation and macular dystrophy were observed at fundus examination. Standard electroretinography showed normal scotopic and photopic responses. OCT revealed high reflectivity across the fovea without depression. The typical OCT pattern led us to direct the molecular analysis towards the genes involved in oculocutaneous albinism. The molecular analysis identified mutations in the TYR gene. Conclusion: In this case, the role of OCT was crucial in guiding the molecular analysis for the diagnosis of albinism. OCT is therefore instrumental in similar cases that do not present typical characteristics of a disease. The case also proves the relevance of molecular analysis to confirm clinical diagnoses in hereditary retinal diseases.